The Foundations and Political Principles deriving from The Prophetic Documents - Aldaradkeh , Khaleel; Abu Jraiban, Mohammad (Jordan Journal of Islamic Studies, 2023)
This study examines the principles and foundations of political principles derived from a collection of prophetic documents, their areas of application in state policy, their external relations during the prophetic era, as well as the security measures and strategic actions taken to implement the policies articulated in these documents. The study employs a descriptive historical approach and an inductive analytical method to arrive at conclusions and recommendations that highlight the significance of these documents, as they encompass just, security, political, and constitutional systems relevant to the entire world. Furthermore, the researchers recommend the study and application of the insights gained from these documents, particularly for those with an interest in advocacy and political affairs.